The role of the family and formal education in the development of the broken home child's thought and morals - Prihatini Septi Dayani; Haryono Haryono (Edu Sociata : Jurnal Pendidikan Sosiologi, 2021)
Education is a broader process of increasing knowledge, insight and process of shaping a broader character and mind-set. Formal education can transform one's self into a more disciplined, know - the - rules and limditations of doing things. With formal education we can raise awareness of a thing that can sometimes lead one toward something that is wrong. Education can also help a person to become critical in his or her thinking. Education can help a person change his weaknesses into strengths. In the world of education there is a great deal of implied meaning and purpose, hope and goals to achieve. One dof the professions that play a major role in education is teachers. Teachers are a milestone in the success and development of education. Education is especially important for children who receive little love from their parents and for children who are victims of a parent's divorce.